2016
DOI: 10.1093/schbul/sbw055
|View full text |Cite
|
Sign up to set email alerts
|

A Network Approach to Psychosis: Pathways Between Childhood Trauma and Psychotic Symptoms

Abstract: Childhood trauma (CT) has been identified as a potential risk factor for the onset of psychotic disorders. However, to date, there is limited consensus with respect to which symptoms may ensue after exposure to trauma in early life, and whether specific pathways may account for these associations. The aim of the present study was to use the novel network approach to investigate how different types of traumatic childhood experiences relate to specific symptoms of psychotic disorders and to identify pathways tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
295
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(343 citation statements)
references
References 71 publications
18
295
0
13
Order By: Relevance
“…For one, it was found that a more densely connected network at baseline predicts the presence of depression at follow up [16]. Within the field of psychosis, network analysis revealed the relationship between childhood trauma and psychotic symptoms [17]. For individual suicidal patients, the main asset lies in the fact that they can get insights in their own unique personalized network, making personalized treatment and safety planning much more likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For one, it was found that a more densely connected network at baseline predicts the presence of depression at follow up [16]. Within the field of psychosis, network analysis revealed the relationship between childhood trauma and psychotic symptoms [17]. For individual suicidal patients, the main asset lies in the fact that they can get insights in their own unique personalized network, making personalized treatment and safety planning much more likely.…”
Section: Discussionmentioning
confidence: 99%
“…A network perspective can help us understand how risk factors for suicidal behaviour such as intensity of suicidal thoughts and impulsivity interact and how their interaction is related to future suicidal behaviour. Within the field of psychopathology, it has been applied to the field of depression [16], psychosis [17] and Post Traumatic Stress disorder [18] , but not yet to the field of suicidology. As suicidal behavior is argued to be trans diagnostic [19]and the end result of the highly complex interaction between many factors [3], it is highly suited to be analyzed from a network perspective.…”
Section: From Latent Variable Modelling To Network Analysismentioning
confidence: 99%
“…Los nodos pueden ser todo tipo de variables como, por ejemplo, síntomas psicopatológicos, rasgos de personalidad, o estímulos ambientales (p. ej., experiencias traumáticas, consumo de cannabis) (Isvoranu et al, 2017;Klippel et al, 2017). También podría ser algún otro tipo de variable procedente de niveles de análisis no observables al ojo humano (p.…”
Section: Conceptos Básicos En El Análisis De Redes Psicológicasunclassified
“…Las temáticas de estudio bajo el modelo de redes se encuentran en clara ebullición y expansión. Sirva como muestra los trabajos que han analizado la sintomatología depresiva (Bringmann, Lemmens, Huibers, Borsboom, y Tuerlinckx, 2015;Cramer et al, 2016;Fried, van Borkulo, Epskamp, et al, 2016), la psicosis y su relación con experiencias traumáticas o impactos ambientales (Isvoranu, Borsboom, van Os, y Guloksuz, 2016;Isvoranu et al, 2017), los síntomas psicóticos negativos (Levine y Leucht, 2016), los síntomas psicóticos atenuados (Fonseca-Pedrero, 2018), el abuso de sustancias (Rhemtulla et al, 2016), la calidad de vida (Kossakowski et al, 2016), los sínto-mas de estrés post-traumático (McNally et al, 2014), la comorbilidad (Cramer, Waldorp, van der Maas, y Borsboom, 2010), la relación entre síntomas y trastornos desde los sistemas taxonómicos (Boschloo et al, 2015;Tio, Epskamp, Noordhof, y Borsboom, 2016), los problemas emocionales y comportamentales en adolescentes (Boschloo, Schoevers, van Borkulo, Borsboom, y Oldehinkel, 2016;Fonseca-Pedrero, 2017) o la inteligencia (Maas, Kan, Marsman, y Stevenson, 2017), por citar algunos. Borsboom (2017) ha propuesto un modelo teórico de redes para la comprensión de los trastornos mentales.…”
Section: Algunas Aplicaciones Al Campo De La Psicologíaunclassified
“…This approach conceptualizes symptoms as mutually interacting, often reciprocally reinforcing, elements of a complex network [54,55]. Network analysis have been successfully used in the field of psychosis [56], personality research [57] and depression [58], contributing to advances in psychopathology research. For instance, non-DSM symptoms of depression (e.g.…”
Section: Imv Model and Analysis In The Caspar Studymentioning
confidence: 99%